High-resolution ethograms, accelerometer recordings, and behavioral time series of Japanese quail - Simian, Catalina (2024)
Fil: Simian, Catalina. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.